Postponed healthcare in The Netherlands during the COVID-19 pandemic and its impact on self-reported health - Visscher, Kirsten; Kouwenberg, Lisanne H. J. A.; Oosterhoff, Marije; Rotteveel, Adriënne H.; de Wit, G. Ardine (Frontiers in Health Services, 2023)
Background: Healthcare services have been seriously disrupted during the COVID-19 pandemic. The aim of this study was to examine the extent to which Dutch citizens have experienced postponed healthcare and how this affected their self-reported health. In addition, individual characteristics that were associated with experiencing postponed healthcare and with self-reported negative health effects were investigated. Methods: An online survey about postponed healthcare and its consequences was developed, and sent out to participants of the Dutch Longitudinal Internet Studies for the Social sciences panel (N=2.043). Data were collected in August 2022. Multivariable logistic regression analyses were carried out to explore characteristics associated with postponed care and self-reported negative health outcomes. Results: 31% of the panel experienced postponed healthcare, either initiated by the healthcare provider (14%), on their own initiative (12%) or as a combination of both (5%). Postponed healthcare was associated with being female (OR = 1.61; 95% CI = 1.32 ; 1.96), presence of chronic diseases (OR = 1.55, 95% CI = 1.24 ; 1.95), high income (OR = 0.62, 95% CI = 0.48 ; 0.80) and worse self-reported health (poor vs. excellent OR = 2.88, 95% CI = 1.17 ; 7.11). Overall, 40% experienced temporary or permanent self-reported negative health effects due to postponed care. Negative health effects as a result of postponed care were associated with presence of chronic conditions and low income levels (p<0.05). More respondents with worse self-reported health and foregone healthcare reported permanent health effects as compared to those with temporary health effects (p<0.05). Discussion: People with poor health are most likely to experiencing postponed healthcare and negative health consequences as a result. Furthermore, those with negative health consequences decided to forego health by themselves more often. As part of long-term plans to maintain the accessibility of healthcare services, specific attention should be paid to reaching out to people with a vulnerable health status.